THE COMPARISON OF CREDIT ACCESSIBILITY CHANNEL ON SATISFACTION AND LOYALTY: CASE STUDY OF CREDIT CONSUMER “GENERATION X AND Y” IN THAILAND - Srisornkompon, Palida (UI Scholars Hub, 2021)
Manuscript type: Research articleResearch aims: The study aimed to compare the effects of credit accessibility channels on satisfaction and loyalty between credit users in generations X and Y. Design/methodology/approach: The sample groups were as follows: 1)138 credit users in generation X (n = 138) and, 2) 262 credit users in generation Y (n =262). The data were analyzed using the AMOS program via the structure equation modeling (SEM) technique. Research findings: The online channel showed the positive influence of satisfaction in both the generation X and Y groups. The results also indicated that generation Y credit users exhibited higher satisfaction after using online channels than generation X credit users did.Theoretical contribution/originality: The study classified target groups into generation X and Y to identify satisfaction and loyalty in the banking industry. The findings can be used for determining and managing the channel strategy to align with their target group’s generation. Practitioner/policy implications: The usage of an online channel could not generate loyalty. Therefore, the bank should focus on establishing the reliability and credibility of the online channel, which will ultimately result in satisfaction and loyalty to the bank.Research limitation/implications: The researcher focused on credit channels affecting consumers’ satisfaction and loyalty. Future research should concentrate on other marketing factors, such as credit conditions and service availability.